2005
DOI: 10.1152/ajprenal.00190.2004
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the energy sensor AMP-activated protein kinase in the kidney by dietary salt intake and osmolality

Abstract: The AMP-activated protein kinase (AMPK) is a key controller of cellular energy metabolism. We studied its expression and regulation by salt handling in the kidney. Immunoprecipitation and Western blots of protein lysates from whole rat kidney using subunit-specific antibodies showed that the alpha1-catalytic subunit is expressed in the kidney, associated with the beta2- and either gamma1- or gamma2-subunits. Activated AMPK, detected by immunohistochemical staining for phospho-Thr172 AMPK (pThr172), was express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
61
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 59 publications
8
61
5
Order By: Relevance
“…14,15 Surprisingly, we found that AMPK phosphorylation in RMICs was transiently increased at 5 minutes, then rapidly decreased by hypertonicity within 12 hours, and then gradually returned to baseline levels, which is in sharp contrast to a previous report suggesting that hyperosmolality activated AMPK in MMDD1 cells, a clonally derived macula densa cell line, within 30 minutes. 15 This inhibitory effect on AMPK activity appears to be specific for RMICs, because hypertonicity significantly increased AMPK activity in IMCD-3 cells, which is consistent with a previous report in MDCK cells. 32 The mechanism by which hypertonicity suppresses AMPK phosphorylation in RMICs is currently unknown.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…14,15 Surprisingly, we found that AMPK phosphorylation in RMICs was transiently increased at 5 minutes, then rapidly decreased by hypertonicity within 12 hours, and then gradually returned to baseline levels, which is in sharp contrast to a previous report suggesting that hyperosmolality activated AMPK in MMDD1 cells, a clonally derived macula densa cell line, within 30 minutes. 15 This inhibitory effect on AMPK activity appears to be specific for RMICs, because hypertonicity significantly increased AMPK activity in IMCD-3 cells, which is consistent with a previous report in MDCK cells. 32 The mechanism by which hypertonicity suppresses AMPK phosphorylation in RMICs is currently unknown.…”
Section: Discussioncontrasting
confidence: 99%
“…In fact, almost all subunits of AMPK can be found in the kidney, and activated AMPK was found strongly expressed at the apical surface of cortical thick ascending limbs and the macula densa. 15 However, the detailed expression profile of AMPK and its activity in each cell type of the kidney is still under investigation. This study demonstrates constitutive expression of AMPK in RMICs, where its activity is essential for determining the survival of RMICs under the hypertonic condition both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The actions of AMPK are complex as this kinase regulates a number of transport proteins involved in secretion or absorption of electrolytes in epithelia. Thus epithelial Na ϩ channels (30 -32), the renal NKCC2 (33,34), CFTR (5-7), and probably the secretory Na (34) can all be controlled by AMPK. Regulation occurs either indirectly, as in the case of epithelial Na ϩ channels (ENaC), or directly through AMPK phosphorylation as for CFTR, NKCC2, and probably NKCC1.…”
Section: Discussionmentioning
confidence: 99%